Injury profile of an elite male football team from the Turkish Super League for two consecutive seasons - Kurklu, G. B.; Yargic, M. P. (Medicina dello Sport, 2020)
BACKGROUND: Injury profiles of football teams vary according to the level of competition and geographical region. However, there is so far no available injury surveillance data from the Turkish Super League. The aim of this study was to provide a two-season-long, detailed injury profile (injury rate, injury locations, injury severity and injury burden) of an elite Turkish Super League team, which also joined the UEFA Europa League in the second season and to make a comparison of the two seasons. METHODS: Injury records of a Turkish Super League team were kept for two consecutive seasons (2015-2016 and 2016-2017). Injury rates (overall, training and match), types, locations, severity, and burden were analyzed. RESULTS: Rate of injury per 1000h was 6.45 in 2015-2016, and 6.62 in 2016-2017 (P>0.05). Total injury burden per 1000h increased by 42.87% (from 38.74 in 2015-2016 to 55.35 in 2016-2017). Match injury burden was 61.72 in 2015-2016, and 117.56 in 2016-2017, increasing by 90.47%. Injuries to the lower limbs were the most common in both seasons. CONCLUSIONS: Important differences were observed in injury rates and burden in comparison with other leagues from different countries. Also, team injury burden increased dramatically in the second season.